The Reintegration Experiences of Young Indonesian Returnees in a Globalizing World - Salsabila, Alifia; Wulandari, Astri (eProceedings of Management, 2025)
This study, The Reintegration Experiences of Young Indonesian Returnees in a Globalizing World, examinesdifferences in communication styles, message interpretation, and attitudes between Indonesians living abroad andthose in Indonesia. As globalization drives migration and cultural exchange, understanding interculturalcommunication nuances becomes increasingly vital. The research explores reintegration challenges faced byreturning Indonesians, emphasizing shifts in communication dynamics, conflict management styles, and emotionalexperiences. Using a qualitative approach based on Cultural Communication Theory, in-depth interviews wereconducted with individuals who have lived both overseas and in Indonesia. These interviews reveal how culturalidentity evolves through expatriate experiences, significantly influencing interpersonal communication.Participants shared narratives highlighting notable changes in self-construal and interaction styles uponreturning. The study identifies key differences as potential sources of misunderstandings and conflicts whenreengaging with local communities that have evolved in their absence. The findings illustrate the complexinterplay between cultural context and individual identity, offering insights into the emotional aspects ofreintegration.This research contributes to intercultural communication discussions while providing practicalrecommendations for individuals, families, and organizations to facilitate smoother transitions. Ultimately, itpromotes a deeper understanding of cultural adjustment, fostering greater tolerance and harmony withinIndonesian society.Keywords4 Cultural Reintegration; Inter-Cultural Communication; Indonesian Returnees